Assessing nursing quality in paediatric intensive care units: a cross‐sectional study in China. Issue 6 (23rd May 2016) - Zhang, Yuxia; Liu, Linxia; Hu, Jing; Zhang, Yanhong; Lu, Guoping; Li, Guangyu; Zuo, Zelan; Lu, Hua; Zou, Huan; Wang, Zaihua; Huang, Quelan
ABSTRACT: Background: Nursing‐sensitive indicators are considered effective tools for improving the quality of care in hospitals. However, these have not been used in paediatric intensive care units (PICUs) in China. Aim: To develop nursing‐sensitive indicators for PICUs and to assess the quality of nursing in PICUs in China based on the nursing‐sensitive indicators. Design: Multi‐centre, cross‐sectional study. Methods: Structure, process and outcome indicators were developed and measured from 1 January to 31 March 2014 in seven PICUs in China. Results: The structure indicators showed that one nurse cared for an average of 2·8 patients in a PICU, and 44% of nurses had a bachelor's degree. The process indicators revealed that hand‐washing compliance varied across PICUs, whereas pain management and physical restraint have not been adequately addressed in China. The outcome indicators revealed that the incidence rates of ventilator‐associated pneumonia and central‐line‐associated blood stream infections were 2·96 and 0·7, respectively, per 1000 device days. Patients were intubated for a total of 4392 mechanical ventilator days, and 32 patients (7·29‰) had an unplanned extubation. Nurses were moderately satisfied in their jobs (3·1 ± 0·3), and parents reported that nurses provide high quality of care. Conclusions: This study developed and used nursing‐sensitive indicators to assess the quality of nursing in PICUs in China, which provided a reference for national and international comparisons of nursing quality in PICUs. Nursing staffing levels and education should be improved. Pain management and physical restraints should be regulated in China's PICUs. Nurse managers need to explore staff attitudes towards implementation of family‐centred care. The development of a national database of nursing quality indicators can contribute to quality and safety improvement. Relevance to clinical practice: This study developed a set of nursing‐sensitive indicators, and these indicators were used to assess and improve the quality of nursing in PICUs.